Effects of 8 weeks of strength training to the sprint abilities at the end of the race for endurance athletes - Varjus, R.; Mikkola, J.; Ahtiainen J. (19th International Symposium "Modern Science and Practice for Strength and Endurance Training" October 10-12, 2018, 2020)
In the most endurance events, strength/speed/anaerobic characteristics have become increasingly important for endurance athletes when sprinting at the end of a race. Previous studies have shown that strength training could have positive impact for the endurance athletes` sprint abilities at the end of the racea,b. The aim of this study was to find out if eight weeks planned strength training affected to endurance athletes` capabilities at the end of the race.